Volumetric change of the latissimus dorsi muscle after postoperative radiotherapy in immediate breast reconstruction with an extended latissimus dorsi musculocutaneous flap - Tae Seo Park (Archives of Plastic Surgery, 2020)
Background This study aimed to determine the magnitude of volume reduction of the latissimus dorsi (LD) muscle after treatment using only postoperative radiotherapy (PORTx) in patients who underwent immediate breast reconstruction using an extended LD musculocutaneous (eLDMC) flap after partial mastectomy. Methods We retrospectively reviewed 28 patients who underwent partial mastectomy and an eLDMC flap, received only PORTx, and underwent chest computed tomography (CT) 7 to 10 days after surgery and 18±4 months after the end of radiotherapy, from March 2011 to June 2016. The motor nerve to the LD was resected in all patients. One plastic surgeon performed the procedures, and the follow-up period was at least 36 months (mean, 46.6 months). The author obtained LD measurements from axial CT views, and the measurements were verified by an experienced radiologist. The threshold for statistical significance was set at P<0.05. Results A statistically significant decrease in the LD volume was found after the end of PORTx (range, 61.19%–80.82%; mean, 69.04%) in comparison to the measurements obtained 7 to 10 days postoperatively (P<0.05). All cases were observed clinically for over 3 years. Conclusions The size of an eLDMC flap should be determined considering an average LD reduction of 69% after PORTx. Particular care should be taken in determining the size of an eLDMC flap if the LD is thick or if it occupies a large portion of the flap.